(untitled) (Research, Society and Development, 2021)
Cervical cancer is considered a public health problem in the country, where it has shown high incidence rates, with about 15,590 new cases. From this increase, the need to discuss prevention, tracking, early detection and treatment is perceived. Some factors contribute to the emergence of cervical cancer, early sexual intercourse, a large number of children and recurrence of gynecological infections. Preventive examination is a means of screening to identify some type of change in the cervix. The objective of this work is to know about the services of Basic Health Units in rural areas, identifying the difficulties faced by rural women regarding the performance of preventive examinations for cervical cancer. A bibliographic review was carried out, exploratory with a qualitative approach, with journals published from 2012 to 2020. The Family Health Strategy team in the rural area finds it difficult to provide care efficiently, where, given the difficulties encountered, teams rarely go to the units to carry out actions and assistance and when they do, sometimes the team is incomplete. Not to mention, they are often unable to meet all the demand, due to the short time for service. Therefore, we can say that, since they live in rural areas, these women are often not attended to by medical appointments, preventive and cytopathological exams, as well as other health demands.